Opening remarks - Kivalov, S. V.; Kivalov, Serhii; Kivalov, Sergiy; Kivalov, S.; Ківалов, Сергій Васильович; Ківалов, С. В. (Одеса : НУ «ОЮА», 2026)
The foreword outlines the current trends in the development of criminalistics in the context of digital transformation, the rapid advancement of artificial intelligence technologies, and the emergence of global security challenges. It emphasizes the need to reconsider the role of criminalistics as an interdisciplinary field of knowledge integrating legal doctrine, forensic science, information technologies, and analytical methods to ensure the effective administration of criminal justice. Particular attention is paid to the use of digital evidence, the documentation of war crimes, the investigation of cybercrime, the application of artificial intelligence technologies, and the importance of international cooperation in the field of criminalistics. The author highlights the significance of international academic dialogue for developing modern approaches to criminal investigations and advancing criminalistics in the digital era.
Kivalov S. Opening remarks. Криміналістика майбутнього: цифрові інновації, штучний інтелект, глобальні виклики та загрози : збірник матеріалів міжнар. наук.–практ. конф. (м. Одеса, 5 черв. 2026 р.)=Criminalistics of the Future: Digital Innovations, Artificial Intelligence, Global Challenges and Threats: Proceedings of the International Scientific and Practical Conference (Odesa, 5 June 2026) / заг. ред. С. Ківалова, М. Аракеляна. Одеса : НУ «ОЮА», 2026. С. 38-39. URL: https://doi.org/10.32837/11300.33644
Keywords: criminalistics; digital criminalistics; digital evidence; artificial intelligence; forensic science; cybercrime; war crimes investigation; criminal proceedings; international cooperation; digital justice; криміналістика; цифровізація; цифрові докази; штучний інтелект; судова експертиза; кіберзлочинність; воєнні злочини; кримінальне судочинство; міжнародне співробітництво; цифрова трансформація правосуддя